2017
DOI: 10.21037/atm.2017.06.15
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as emerging non-invasive biomarkers for gliomas

Abstract: No single circulating biomarker has been put to practice for malignant gliomas so far, the most lethal primary brain tumors. Many promising protein biomarkers such as the mutant EGFRvIII or glial fibrillary acidic protein (GFAP) have already been detected in the blood and cerebrospinal fluid (CSF) of patients with gliomas, but their clinical value is still pending validation. Furthermore, these and other proteins seem to lack sufficient sensitivity and specificity required for a successful biomarker in this cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In the last few years, great effort has been put into searching for diagnostic, prognostic, predictive, and therapeutic response biomarkers in glioma patients [16]; however, so far, no single circulating biomarker has been used in routine practice for management of these patients [17]. The search for these kinds of biomarkers still represents an exciting research area; therefore, the aim of the current study was the evaluation of serum and CSF concentrations of CCL2, IL-8, and ICAM-1 in patients with neuroepithelial tissue tumors as compared to non-tumoral patients, with no history of cancer as a comparative group.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, great effort has been put into searching for diagnostic, prognostic, predictive, and therapeutic response biomarkers in glioma patients [16]; however, so far, no single circulating biomarker has been used in routine practice for management of these patients [17]. The search for these kinds of biomarkers still represents an exciting research area; therefore, the aim of the current study was the evaluation of serum and CSF concentrations of CCL2, IL-8, and ICAM-1 in patients with neuroepithelial tissue tumors as compared to non-tumoral patients, with no history of cancer as a comparative group.…”
Section: Introductionmentioning
confidence: 99%
“…MiR146a and miR26a were upregulated in the vitreous humor of uveal melanoma patients [ 16 ], and follow-up studies revealed miR146a was also upregulated in blood serum exosomes of uveal melanoma patients [ 17 ]. Additionally, systemic miRNAs are being investigated as biomarkers for malignant gliomas [ 18 ]. In brain tissue, miRNA expression is up- or downregulated for numerous miRNA with glioma onset and progression, and preliminary clinical data suggests circulating miRNA may serve as a biomarker for glioma diagnosis and prognosis.…”
Section: Evs As Biomarkers In the Visual Systemmentioning
confidence: 99%
“…GC is one of the leading causes of cancer-associated mortality due to late diagnosis and limited therapeutic strategies. Circulating miRNAs are promising, noninvasive biomarkers for cancer screening (17). The present study reported an investigation on miR-650 expression in human GC.…”
Section: Discussionmentioning
confidence: 87%